The dynamics and existence of Islamic party in 2019 general election: case study of Prosperous Justice Party (PKS) - Muh Haris; Yuwanto Yuwanto; Teguh Yuwono; Nur Hidayat Sardini (Indonesian Journal of Islam and Muslim Societies, 2020)
The development of Islam in the political arena in Indonesia is interesting to be analyzed comprehensively. The purpose of this paper is to analyze the existence of Islamic political parties after the 2019 simultaneous general elections. The main problem in political life in Indonesia is the decline of public trust in political parties. One of the main reasons is the corruption case that ensnared politicians. The presence of Islamic political parties is hopefully able to bring a change and alter the ugly stigma from the society towards the political parties. This study is qualitative in nature with a case study of PKS as a participant in the 2019 simultaneous general election, using an institutional assessment of the existence of political parties. The dynamics and existence of PKS before the 2019 general election were categorically high. It means that the PKS movement was active in society by offering strategic programs and policies for voters. PKS has a structured party system starting from the regeneration system to constituent treatment that can increase the number of voters in the 2019 elections. This research shows that regeneration carried out through tarbiyah can instill party ideology in cadres, but fails to raise the party in a fast time. Based on the political dynamics of PKS during the Jokowi-JK administration period 2014-2019, identity politics was able to increase voter participation and increase PKS votes in the 2019 elections.